The Main Character's Personality in the Novel "Tinta Terakhir" by Narandara: A Psychological Literature Study - Homsah; Nurbaini Futuhat Wulansari (LITERATUR : Jurnal Bahasa dan Sastra, 2025)
This research aims to analyze the personality of the main character in the novel Tinta Terakhir by Narandara through a literary psychology approach using Gerard Heymans' personality theory. The research method used is qualitative with a descriptive approach. Data were obtained through text analysis of the novel, including dialogues and narratives that depict the main character's personality. The results show that the main character in this novel has a complex and dynamic personality, which can be broken down into Heymans' personality typology. The main character exhibits traits of emotionality, activity, and secondary processes. Emotionality is shown through intense emotional reactions to events in the story. Activity is reflected in the actions and decisions taken by the main character in facing conflicts and challenges. Secondary processes or auxiliary functions are seen in the main character's ability to adapt and show empathy towards other characters. This research contributes to understanding the characterization of the main character in Indonesian literature through the lens of literary psychology, and enriches literary studies with the application of Gerard Heymans' personality theory. These findings are expected to serve as a reference for future research in the fields of literary and psychological studies